2002
DOI: 10.1159/000051527
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Oxidative Stress in the Pre- and Perinatal Period

Abstract: Oxidative stress may be defined as an imbalance between pro-oxidant and antioxidant forces resulting in an overall pro-oxidant insult. Pregnancy is a physiological state accompanied by a high energy demand of many bodily functions and an increased oxygen requirement. Because of the increased intake and utilization of oxygen, augmented levels of oxidative stress would be expected. Arguments for a role of oxidative stress/oxidative lipid derivatives in the pathogenesis of preeclampsia are documented in many pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
162
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(170 citation statements)
references
References 114 publications
3
162
0
5
Order By: Relevance
“…Placental production of lipid peroxides decreases as normal gestation advances, most likely because of an increase in the activity of superoxide dismutase and catalase [27]. Placental antioxidant defense is considered sufficient to control lipid peroxidation in healthy pregnancy [23]. Our data showed that there was a discrepancy between the levels of oxidative DNA damage and lipid peroxidation at delivery.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Placental production of lipid peroxides decreases as normal gestation advances, most likely because of an increase in the activity of superoxide dismutase and catalase [27]. Placental antioxidant defense is considered sufficient to control lipid peroxidation in healthy pregnancy [23]. Our data showed that there was a discrepancy between the levels of oxidative DNA damage and lipid peroxidation at delivery.…”
Section: Discussionmentioning
confidence: 62%
“…Moreover, the placenta is a major source of oxidative stress because of its enrichment with PUFA [23]. Falkay et al suggested that the increase in the lipid peroxide levels was due to the increased prostaglandin synthesis in the placenta [24].…”
Section: Discussionmentioning
confidence: 99%
“…Since pregnancy is a high metabolic state and accompanied by elevated requirement for tissue oxygen, women with pregnancies are more subject to the oxidative stress compared to the non-pregnant women [5]. A deficient detoxification system in pregnant women may result in the RSA due to the increased exposure of embryo to exogenous and endogenous compounds.…”
Section: Introductionmentioning
confidence: 99%
“…As pregnancy and fetal growth progress, an overproduction of ROS in placental and fetal mitochondria is observed (Kim et al 2005). It is thought that the placenta is a major source of oxidative stress in pregnant females (Gitto et al 2002, Myatt and Cui 2004, Hung et al 2010. A significant part of the total indicators of pregnancy-related oxidative stress may derive from the placenta's mitochondrial mass, which increases with gestational age (Wang and Walsh 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy is a period when oxidative stress can be expected due to the high energy demand and increased oxygen requirement, together with the increased metabolic activity in placental mitochondria (Gitto et al 2002). Evidence for this concept can be found in studies demonstrating elevated levels of oxidative stress markers during normal pregnancy in women (Wickens at al.…”
Section: Introductionmentioning
confidence: 99%